Deciphering the role of neddylation in tumor microenvironment modulation: common outcome of multiple signaling pathways - Dequan Liu; Xiangyu Che; Guangzhen Wu (Biomarker Research, 2024)
Abstract Neddylation is a post-translational modification process, similar to ubiquitination, that controls several biological processes. Notably, it is often aberrantly activated in neoplasms and plays a critical role in the intricate dynamics of the tumor microenvironment (TME). This regulatory influence of neddylation permeates extensively and profoundly within the TME, affecting the behavior of tumor cells, immune cells, angiogenesis, and the extracellular matrix. Usually, neddylation promotes tumor progression towards increased malignancy. In this review, we highlight the latest understanding of the intricate molecular mechanisms that target neddylation to modulate the TME by affecting various signaling pathways. There is emerging evidence that the targeted disruption of the neddylation modification process, specifically the inhibition of cullin-RING ligases (CRLs) functionality, presents a promising avenue for targeted therapy. MLN4924, a small-molecule inhibitor of the neddylation pathway, precisely targets the neural precursor cell-expressed developmentally downregulated protein 8 activating enzyme (NAE). In recent years, significant advancements have been made in the field of neddylation modification therapy, particularly the integration of MLN4924 with chemotherapy or targeted therapy. This combined approach has demonstrated notable success in the treatment of a variety of hematological and solid tumors. Here, we investigated the inhibitory effects of MLN4924 on neddylation and summarized the current therapeutic outcomes of MLN4924 against various tumors. In conclusion, this review provides a comprehensive, up-to-date, and thorough overview of neddylation modifications, and offers insight into the critical importance of this cellular process in tumorigenesis.